PEOPLE PERCEPTIONS AND THEIR BEHAVIORS IN SPORTS (Global Journal of Human-Social Science, 2010)
This research is conducted to determine people's attitudes towards sports, how much they make use of the sports facilities around, and the relationship between their personal characteristics and sports habits. In the research, a questionnaire composed of X questions is conducted. The participants are 62% male, 63% between the ages 22-39, 76% single and 83% undergraduates/graduates. A correlation analysis is done to put forward the relationship between the participants' personal characteristics and how often they do sports. According to the results of the research, out of the five personality dimensions, only awareness of responsibility and sociability dimensions are highly related to the participants' frequency of doing sports. Accordingly, as one's awareness of responsibility and sociability rise, their frequency of doing sports rise as well.